Pelaksanaan Perjanjian Gadai Pada PT. Pegadaian UPC. Tanjung Seneng Bandar Lampung - Male, Martina; Nadriana, Lenny; Fukuyama, Diena; Renaldy, Rendy (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Pawn agreements at this time are agreements that are often carried out by the majority of people in order to fulfill a growing number of needs, the same is true for the services of PT. UPC Pawnshop. Tanjung Seneng Bandar Lampung, which provides solutions to people who are in need of funds by only providing a guarantee of valuable objects that have a value that matches the loan. In practice, several things become the subject of the problems discussed in this study, namely whether the form of a pawning agreement at PT. UPC Pawnshop. Tanjung Seneng and how is the settlement of non-performing loans at PT. Pegadaian UPC Tanjung Seneng.Efforts made in discussing and solving the problems in this study were carried out using two kinds of approaches, namely juridical/normative and empirical approaches. The normative approach is carried out by studying and reviewing the provisions in the form of laws and regulations that apply in a formal juridical manner relating to the implementation of mortgage agreements and efforts to settle problem loans at PT. Pegadaian UPC Tanjung Seneng. While the empirical approach is carried out by looking at the facts that apply to legal regulations related to the implementation of pawn agreements. The data sources used in this research are primary data and secondary data. The research phase includes library research, namely research intended to obtain secondary data and field research, namely a way to obtain primary data to support secondary data. Data collection techniques include document studies and interviews. Data collection tools in library research are in the form of notes on the results of an inventory of legal materials and data collection tools in field research are in the form of a list of questions, then recorded via a tape recorder and flash disk. Data analysis using juridical-qualitative method.The form of a pawn agreement at PT. UPC Pawnshop. TanjungHappy applies the standard form of agreement, the pawnshop has prepared all the requirements by default in the form, and contained in the Credit Proof (SBK) and Pawning Proof (SBG) with the intention that the borrower must agree to all the terms contained in the form. The form of a standard agreement does not conflict with statutory regulations, because the Civil Code and other statutory provisions also do not prohibit a person from making an agreement in the particular form he wants. Settlement of problem loans at PT. UPC Pawnshop. TanjungHappy is through persuasive efforts.